2020
DOI: 10.1097/yco.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology for management of severe mental disorders in low-income and middle-income countries

Abstract: Purpose of review Increasingly, digital technologies, especially mobile telecommunications and smartphone apps, are seen as a novel tool for managing severe mental disorders (SMDs) in low-income and middle-income countries (LMICs). However, there is a need to identify best practices in the use of digital technologies to effectively reach, support, and manage care for patients living with SMDs. In this review, we summarize recent studies using digital technology to manage symptoms and support clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 38 publications
1
34
0
2
Order By: Relevance
“…Our study aligns with an emphasis in the digital mental health research literature that it is necessary to consider the perspectives of users in order to support adoption, engagement, and sustained use of digital interventions [65][66][67]. Despite the large number of technical challenges that participants mentioned throughout this pilot study, we were reassured by participants' continued interest in learning about the mental health treatment related content.…”
Section: Discussionsupporting
confidence: 52%
“…Our study aligns with an emphasis in the digital mental health research literature that it is necessary to consider the perspectives of users in order to support adoption, engagement, and sustained use of digital interventions [65][66][67]. Despite the large number of technical challenges that participants mentioned throughout this pilot study, we were reassured by participants' continued interest in learning about the mental health treatment related content.…”
Section: Discussionsupporting
confidence: 52%
“…Other recent reviews have focused merely on the exploration of COVID-19 mobile apps in app stores in general [ 8 ] or were restricted to apps deployed in specified countries such as the United States, the United Kingdom, and India [ 9 ]. Although there are already related generic COVID-19 information and communication technology surveys [ 10 , 11 ], they focus on specific topics such as contact tracing [ 12 , 13 ]; specialized health sectors like pediatric health care delivery [ 14 ], mental health [ 15 ], epilepsy [ 16 ], and palliative care [ 17 ]; or countries like India [ 14 ], China [ 18 ], and the United Kingdom [ 19 ]. To the best of our knowledge, there has been no other work dedicated to the systematic review of pragmatic studies that have demonstrated the real-life use and evaluation of COVID-19 mobile apps.…”
Section: Introductionmentioning
confidence: 99%
“…Digital technology can play an important role in the management of psychiatric illnesses in low- and middle-income countries [ 47 ]. Our multinational team successfully developed and completed the preliminary testing of M-Healer, a novel mHealth intervention designed to be used by healers who provide care to people with psychiatric illnesses in West Africa.…”
Section: Discussionmentioning
confidence: 99%